1950
DOI: 10.1039/jr9500000490
|View full text |Cite
|
Sign up to set email alerts
|

96. Acid-catalysed hydration of acraldehyde. Kinetics of the reaction and isolation of β-hydroxypropaldehyde

Abstract: A kinetic study of the acid-catalysed hydration of acraldehyde to /3-hydroxypropaldehyde (hydracraldehyde ; 3-hydroxypropan-l-al) in aqueous sulphuric acid confirms that the reaction is of the first order with respect to acraldehyde. The rate constants are independent of initial acraldehyde concentration, increase with increasing acid concentration, and are strictly proportional to Hammett's acidity function. /3-Hydroxypropaldehyde, isolated (in poor yield) from the hydration media and characterised as the 3 :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…The mean value corresponds to a half-life of 4.25 (SD = ±1.18) hours at a mean temperature of 21°C (SD = ±2.62). Similar kinetics for acrolein degradation have been shown previously in the laboratory where it was also demonstrated that the rate constants are independent of the initial acrolein concentrations but increase with decreasing pH (hydration) and increasing pH (condensation) (Pressman and Lucas, 1942;Hall and Stern, 1950;Bowmer and Higgins, 1976). The half-life of 46 hours (0.015 hr -1 ) calculated using dilute buffered solutions of acrolein in distilled water at 21 °C and pH 7.0 is considerably longer than the half-life observed in this and other field experiments.…”
Section: Resultssupporting
confidence: 50%
“…The mean value corresponds to a half-life of 4.25 (SD = ±1.18) hours at a mean temperature of 21°C (SD = ±2.62). Similar kinetics for acrolein degradation have been shown previously in the laboratory where it was also demonstrated that the rate constants are independent of the initial acrolein concentrations but increase with decreasing pH (hydration) and increasing pH (condensation) (Pressman and Lucas, 1942;Hall and Stern, 1950;Bowmer and Higgins, 1976). The half-life of 46 hours (0.015 hr -1 ) calculated using dilute buffered solutions of acrolein in distilled water at 21 °C and pH 7.0 is considerably longer than the half-life observed in this and other field experiments.…”
Section: Resultssupporting
confidence: 50%
“…3-HP was purchased from Tokyo Kasei Kogyo Co. Ltd, Tokyo, Japan (TCI America, Portland, OR). Since 3-HPA is not available commercially, it was synthesized chemically from acrolein using the method described by Hall and Stern (1950). Yeast extract (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…1,3-Propanediol is prepared by a two-step process involving the hydrolysis of acrolein to 3-hydroxypropanal followed by hydrogenation [3,38]:…”
Section: Productionmentioning
confidence: 99%